Assessing iron and aluminum-based coagulants for odour and pathogen reductions in sludge digesters and enhanced digestate dewaterability - AKGÜL, DENİZ (ELSEVIER SCIENCE BV, 2017)
Anaerobic digestion (AD) is an effective way of recovering energy and nutrients from organic waste. However, several issues including the production of corrosive, highly odorous and toxic volatile sulfur compounds (VSCs) in digester biogas, and long digestion times to achieve sufficient pathogen reductions can limit its wider adoption. In this study, Kemira (TM) PIX-311 (ferric chloride), PAX XL-6 (aluminum chloride hydroxide sulfate), and PAX XL-19 (polyaluminum chlorohydrate) were added to the digester feeds to evaluate the effects on digester stability, organic removal, VSCs formation in digester headspace, pathogen removal and sludge dewaterability. After preliminary dose trials, two different doses of PIX-311, PAX XL-19, and a 1:1 mixture of PIX-311 and PAX XL-19 were selected. PAX XL-6 was removed from further study as dosing significantly increased VSC levels and the PAX XL-6 dosed digester exhibited signs of instability. During the total operation period of 100 days, addition of PIX-311, PAX XL-19, a combination of PIX-311, PAX XL-19 at concentrations of 4000 and 4500 mg/kg total solids (TS) to digester feed did not lead to process instability. Biogas yields of all metal added digesters were similar to that of the control (no metal addition) digester. PIX-311 achieved up to a 93% reduction in biogas VSCs, 82% better fecal coliform inactivation and exhibited improved dewaterability over the control digester. The PAX XL-19 dosed digester showed modest reductions in biogas VSC concentrations, pathogen levels and improved dewaterability versus the control. Metal addition can be an effective way to control odours from VSCs, pathogens and to improve dewaterability during AD. (C) 2017 Elsevier B.V. All rights reserved.
Keywords: Anaerobic digestion; Volatile sulfur compounds; Biogas; Dewaterability; Fecal coliforms; HYDROGEN-SULFIDE CONCENTRATION; ORGANIC SULFUR-COMPOUNDS; ANAEROBIC-DIGESTION; METHYL MERCAPTAN; SULFATE; INHIBITION; BIOGAS; METHANOGENESIS; BACTERIA